Impact of mechanical bowel preparation on survival after colonic cancer resection. Issue 12 (9th September 2014) - Collin, Å.; Jung, B.; Nilsson, E.; Påhlman, L.; Folkesson, J.
<x xml:space="preserve">Abstract</x> Background A randomized study in 1999–2005 of mechanical bowel preparation (MBP) preceding colonic resection found no decrease in postoperative complications. The aim of the present study was to evaluate the long‐term effect of MBP regarding cancer recurrence and survival after colonic resections. Methods The cohort of patients with colonic cancer in the MBP study was followed up for 10 years. Data were collected from registers run by the National Board of Health and Welfare. Register data were validated against information in patient charts. Cox proportional hazards model was used for multivariable analysis of factors predictive of cancer‐specific survival. Results Register analysis showed significantly fewer recurrences, and better cancer‐specific and overall survival in the MBP group. After validation, 839 of 1343 patients remained for analysis (448 MBP, 391 no MBP). Eighty (17·9 per cent) of 448 patients in the MBP group and 88 (22·5 per cent) of 391 in the no‐MBP group developed a cancer recurrence (P = 0·093). The 10‐year cancer‐specific survival rate was 84·1 per cent in the MBP group and 78·0 per cent in the no‐MBP group (P = 0·019). Overall survival rates were 58·8 and 56·0 per cent respectively (P = 0·186). Conclusion Patients receiving MBP before elective colonic cancer surgery had significantly better cancer‐specific survival after 10 years.